Analisis Manajemen Risiko Aplikasi Customer Operational Center (COC) dengan Menggunakan Metode Nist Sp 800-30: Studi Kasus Pt.Telkom Jakarta Barat - Eva; Badie Uddin (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The Customer Operational Center (COC) information system at PT Telkom has a strategic role in supporting customer service operations, especially in the West Jakarta area. However, the existence of risks that can affect the performance of thisapplication is a challenge that must be managed properly. This research aims to analyze risk management in COC applications using the NIST SP 800-30 approach, a widely recognized method for information technology risk assessment. The research methodology includes asset identification, threats, vulnerabilities, and impact analysis on COC applications. Data was collected through interviews with the operational team, document review, and direct observation of the application work process. The analysis results show several main risks, including disruption to data integrity, the threat of cyber attacks, and the potential for application downtime that could disrupt customer service. Risk mitigation strategies are proposed based on the evaluation results, including implementation of technical controls, information security policies, and increased user awareness. Using the NIST SP 800-30 approach, this research provides systematic insights to increase the resilience of COC applications to risk, as well as supporting operational sustainability and customer service at PT Telkom West Jakarta. It is hoped that these findings can be a practical guide for companies in managing information technology risks on similar platforms.